Perbandingan tingkat efikasi siswa dalam menyelesaikan soal genetika ditinjau dari keikutsertaan bimbingan belajar - Vitta Yaumul Hikmawati; Leo Muhammad Taufik (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
Academic self-efficacy of students makes students confident and confident in their ability to solve genetic problems correctly. The purpose of this study is to compare the level of academic efficacy of students who take tutoring with students who do not take tutoring in solving genetic problems. The research method used, namely quantitative comparative research. The study population was students of class XII in Majalengka Regency. The sample consisted of 240 students who were divided into two groups, namely participant and non-participant tutoring. The research instrument used a questionnaire consisting of 74 items that have been declared valid and reliable statements. Data analysis using two independent sample t-test techniques. The results showed that the comparison of the level of academic efficacy of students in solving genetic problems in terms of participation in tutoring showed a significant difference (p <0.05). Participants tended to have higher levels of academic efficacy on all dimensions of academic efficacy, namely level, strength, and generality compared to non-participants. The conclusion of this study was that there were differences in levels of academic efficacy between students who took tutoring and did not.